Enhancing Self-Confidence and Reducing Public Speaking Anxiety among University Students in Owerri, Nigeria through Structured Training - Lusi Komala Sari; Bede Blaise Chukwunyere Onwuagboke (Jurnal Pengabdian Kepada Masyarakat, 2026)
Low self-confidence in public speaking remains a persistent challenge in higher education, particularly among university students in Owerri, Nigeria. This condition restricts students’ active participation in academic and social contexts, including classroom discussions, oral presentations, and public event facilitation. This community engagement study aimed to examine the effectiveness of structured public speaking training in enhancing students’ public speaking skills and self-confidence. A quantitative approach was employed using a pre-experimental one-group pretest–posttest design, involving 37 university students selected through purposive sampling. The training program was delivered through a structured sequence of theoretical instruction, simulations, guided practice, and systematic feedback. Data were collected using Likert-scale questionnaires and observation sheets and analyzed using paired-sample t-tests. The findings demonstrated a statistically significant improvement in students’ overall public speaking skills following the intervention (t = 5.12, p < 0.001). Notable improvements were observed in performance confidence, speech fluency, content mastery, eye contact, body language, and voice control. These results indicate that structured, practice-oriented public speaking training effectively reduces communication anxiety and strengthens students’ self-confidence. Pedagogically, this study recommends the integration of systematic public speaking training into higher education soft skills development and student empowerment programs.